Blended learning dengan Motivasi Belajar Mahasiswa Universitas Nasional Karangturi Pada Masa Pandemi Covid-19 - Widyastika, Astrid Rizqa; Agustina, Menik Tetha (Psikoborneo: Jurnal Ilmiah Psikologi, 2022)
This study aims to determine the effect of blended learning on the learning motivation of Karangturi National University students during the Covid 19 Pandemic. The data collection method in this study was the saturated sample method. The sampling technique used non-probability sampling with the sampling method of all members of the population as a sample of 30 students. The results of observations and interviews showed that there was a significant negative relationship between blended learning style and student learning motivation during the pandemic, indicating that the better the blended learning style of the students, the lower the student's learning motivation. Vice versa, if the blended learning style is low, the students' learning motivation will be higher. The analysis technique in this study uses correlation analysis. Based on the results of hypothesis testing, it shows that there is a relationship between blended learning and learning motivation, where the correlation coefficient value is Rxy = -0.379 with p = 0.019 (p <0.05). These results indicate that there is a relationship between blended learning and student motivation at the National University of Karangturi Semarang during the Covid 19 Pandemic, showing an R square result of 0.144 so that the effect of blended learning on student learning motivation is 14.4% in this study and 85.6 % influenced by other factors outside this research. Penelitian ini bertujuan untuk mengetahui pengaruh blended learning dengan motivasi belajar mahasiswa Universitas Nasional Karangturi di masa Pandemi Covid 19. Metode pengumpulan data dalam penelitian ini adalah menggunakan metode sampel jenuh. Teknik pengambilan sampel menggunakan non probability sampling dengan metode penarikan sampel semua anggota populasi dijadikan sebagai sampel sebanyak 30 mahasiswa. Hasil observasi dan wawancara menunjukkan bahwa ada hubungan negatif yang signifikan gaya blended learning dengan motivasi belajar mahasiswa di masa pandemi sehingga menunjukkan bahwa semakin baik gaya blended learning mahasiswa maka semakin rendah motivasi belajar mahasiswa. Begitu juga sebaliknya, bila gaya blended learning rendah maka motivasi belajar mahasiswa akan semakin tinggi. Teknik analisis pada penelitian ini menggunakan analisis korelasi. Berdasarkan hasil uji hipotesis, menunjukkan ada hubungan antara blended learning dengan motivasi belajar, dimana nilai koefisien korelasi Rxy = -0,379 dengan p= 0,019 (p< 0,05). Dari hasil tersebut menunjukkan bahwa ada hubungan antara blended learning dengan motivasi belajar mahasiswa Universitas Nasional Karangturi Semarang pada masa Pandemi Covid 19, menunjukkan hasil R square sebesar 0,144 sehingga pengaruh blended learning dengan motivasi belajar mahasiswa sebesar 14,4 % dalam penelitian ini dan 85,6% dipengaruhi faktor-faktor lain di luar penelitian ini.